Manufacturing and Testing of Mulch Sheet from Agricultural Waste Raw Materials - Iswahyudi Iswahyudi; Murdhiani Murdhiani; Milva Dwi Kusuma (University of Prof. Dr. Hazairin, SH, 2022)
This study aims to make sheet organic mulch from several agricultural wastes and determine the best type of material for making sheet organic mulch. This research was carried out at the Greenhouse of the Faculty of Agriculture and the Laboratory of Agrotechnology, Faculty of Agriculture, Samudra University, Langsa City, Aceh Province which took place from February to April 2021.This study used a non-factorial completely randomized design (CRD) with four replications and used several agricultural waste materials consisting of bagasse, water hyacinth, rice straw, corn husks, banana fronds, coconut fiber and empty fruit bunches of oil palm. The raw materials used are agricultural waste 2.4 Kg and NaOH 0.168 Kg. The parameters observed in this study were water absorption, mulch moisture content and mulch yield.The results showed that the type of agricultural waste had a very significant effect on the sheet mulch produced. For water absorption parameters, raw material from bagasse (M1) is the best treatment. As for the water content parameter, the best treatment was found in Coconut Coir (M6) while the best treatment for the mulch yield parameter was found in Rice Straw (M3) agricultural waste.Based on the results of the study, to produce the best sheet mulch, it is recommended to use agricultural waste material from rice straw (M3).